Keeping Fruit In Your Diet - Linda B. Bobroff (EDIS)
“Those of us who love fruit find it hard to imagine that so many Americans eat far less fruit than is recommended for good health. But national surveys show it to be true. Somehow they manage to resist the wonderful textures, aromas, and flavors of melons, berries, apples, bananas, mangoes, and all the other fruits available in this country!” This 2-page radio transcript was written by Linda Bobroff and published by the UF Department of Family, Youth and Community Sciences, March 2012.